2022
DOI: 10.1039/d2dt01380k
|View full text |Cite
|
Sign up to set email alerts
|

New alkaline-earth amidosulfates and their unexpected decomposition to S4N4

Abstract: The amidosulphates Mg(NH 2 SO 3 ) 2 · 4 H 2 O (P2 1 /c), Mg(NH 2 SO 3 ) 2 · 3 H 2 O (P 1̄), Ca(NH...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 88 publications
0
3
0
Order By: Relevance
“…Among the reported sulfamates, the K–N, Rb–N, Cs–N, Sr–N and Ba–N bonds were observed. However, except for the Sr–N bonds in Sr(NH 2 SO 3 ) 2 ( P 2 1 ), 58 as well as the K–N bonds in LiK(NH 2 SO 3 ) 2 , 63 all of the M–N bonds are longer than 3.0 Å with very weak interactions. To understand the relationship between the metal cations and the configuration of [MO x ] polyhedra, the existing 6-coordinate octahedra including [NaO 6 ], [MgO 6 ] and [CdO 4 N 2 ] were compared and discussed based on the HSAB theory.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Among the reported sulfamates, the K–N, Rb–N, Cs–N, Sr–N and Ba–N bonds were observed. However, except for the Sr–N bonds in Sr(NH 2 SO 3 ) 2 ( P 2 1 ), 58 as well as the K–N bonds in LiK(NH 2 SO 3 ) 2 , 63 all of the M–N bonds are longer than 3.0 Å with very weak interactions. To understand the relationship between the metal cations and the configuration of [MO x ] polyhedra, the existing 6-coordinate octahedra including [NaO 6 ], [MgO 6 ] and [CdO 4 N 2 ] were compared and discussed based on the HSAB theory.…”
Section: Resultsmentioning
confidence: 98%
“…4b). The vibration peaks were assigned and are tabulated in Table S11 † according to the calculated and experimental IR vibrations proposed by Höppe et al 58 The similarity and differences between them can be clearly observed. As the most typical difference of the existing water molecules between Cd(NH 2 SO 3 ) 2 •2H 2 O and Cd(NH 2 SO 3 ) 2 , the peaks at 3441 cm −1 and 3368 cm −1 in Cd(NH 2 SO 3 ) 2 •2H 2 O can be assigned to the stretching vibrations of H 2 O, while the peak at 1622 cm −1 is attributed to the bending vibration of H 2 O.…”
Section: Linear Optical Propertiesmentioning
confidence: 99%
“…IR spectra were collected to identify the functional units present in the three compounds (Figure S7). The vibration peaks were assigned and are listed in Table S15, based on previously reported calculated and experimental IR vibrations [7b,10] . Notable distinctions among compounds 1 , 2 , and 3 are evident upon comparison.…”
Section: Resultsmentioning
confidence: 99%